2022
DOI: 10.2147/idr.s368338
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antibacterial Activity and Resistance Prevention of Antimicrobial Combinations for Dihydropteroate Synthase-Carrying Stenotrophomonas maltophilia

Abstract: Background: Stenotrophomonas maltophilia (S. maltophilia) is a multidrug-resistant gram-negative bacillus that is known to be an opportunistic pathogen, particularly in a hospital environment. The infection has a high morbidity and mortality. Sulfamethoxazoletrimethoprim (SXT) is the first-line agent recommended for its treatment. The global spread of dihydropteroate synthase (sul) genes has resulted in an increased resistance rate. However, the appropriate therapy for infections caused by sul-carrying S. malt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
5
1
0
Order By: Relevance
“…Therefore, we can simultaneously use Equations (7) and (8), or other equations established like similar method, to quickly and complementarily predict the rough MPCs from the MIC as references when need. This was further verified by another forty-six data pairs (MIC, MPC) ( Table S7 ) from another five papers [ 42 , 43 , 44 , 45 , 46 ], with an acceptable probability of 91.3%. Conversely, the larger prediction accuracy further confirmed that the MPC of an antimicrobial agent can be roughly calculated from its corresponding MIC.…”
Section: Resultssupporting
confidence: 54%
“…Therefore, we can simultaneously use Equations (7) and (8), or other equations established like similar method, to quickly and complementarily predict the rough MPCs from the MIC as references when need. This was further verified by another forty-six data pairs (MIC, MPC) ( Table S7 ) from another five papers [ 42 , 43 , 44 , 45 , 46 ], with an acceptable probability of 91.3%. Conversely, the larger prediction accuracy further confirmed that the MPC of an antimicrobial agent can be roughly calculated from its corresponding MIC.…”
Section: Resultssupporting
confidence: 54%
“…These data pairs include the MIC and the corresponding MPC, of various antimicrobial agents with different classes against representative pathogenic bacteria, and shown in Table S5. After this, using another forty-six data pairs (MIC, MPC) (Table S6) reported from other papers [38][39][40][41][42], this correlation was further verified by comparison the calculated MPC with the tested one.…”
Section: Correlation Between the Mpc And The Mic Of An Antimicrobial ...supporting
confidence: 58%
“…Thereby, we can simultaneously use equations ( 7) and ( 8), or other equations established like similar method, to quickly and complementarily predict the rough MPCs from the MIC as references when need. This was further verified by another forty-six data pairs (MIC, MPC) (Table S6) from another five papers [38][39][40][41][42], with an acceptable probability of 91.3%. Conversely, the larger prediction accuracy further confirmed that the MPC of an antimicrobial agent can be roughly calculated from its corresponding MIC.…”
Section: Correlation Between the Mpc And The Mic Of An Antimicrobial ...supporting
confidence: 54%
“…To obtain more intuitive visual effects, the correlation analyses were further performed using Microsoft Excel software after these data pairs (MIC, MPC) were respectively transformed into the natural logarithm (log10) of the MIC and the MPC. After this, using another forty-six data pairs (MIC, MPC) (Table S7) reported from other papers [42][43][44][45][46], this correlation was further verified by comparing the calculated MPC with the tested one.4.1.4.…”
Section: Correlation Between the Mpc And The Mic Of An Antimicrobial ...supporting
confidence: 54%
“…Thereby, we can simultaneously use equations ( 7) and (8), or other equations established like similar method, to quickly and complementarily predict the rough MPCs from the MIC as references when need. This was further verified by another forty-six data pairs (MIC, MPC) (Table S7) from another five papers [42][43][44][45][46], with an acceptable probability of 91.3%. Conversely, the larger prediction accuracy further confirmed that the MPC of an antimicrobial agent can be roughly calculated from its corresponding MIC.…”
Section: Correlation Between the Mpc And The Mic Of An Antimicrobial ...supporting
confidence: 54%